Translation, Cultural Adaptation and the Reliability of the Persian Version of Quick Exposure Check Questionnaire - Sahar Abazarpour; Hamid Reza Mokhtarinia; Enayatollah Bakhshi (University of Social Welfare and Rehabilitation Sciences, 2019)
Objective Work-related Musculoskeletal Disorders (MSDs) happen due to risk factors during work, across the world, especially in developing countries. Multiple risk factors (physical, psychosocial and mental) have contributed in MSDs as with most chronic diseases. Several tools are used to evaluate these risk factors. Quick Exposure Check (QEC) is one of the most accurate and quick-response tools for identifying these risk factors. The purpose of the present study is to translate cultural adaptation and to verify the reliability of the Persian-language rapid assessment evaluation checklist. Materials & Methods This study is a methodological study. In this study, the intercultural equivalence of the QEC questionnaire was performed using the international quality of life assessment project. For doing face validity, the questionnaire was completed by 12 ergonomic experts and 15 employees. In this study, (ICC), (SEM), (α Cronbach) The checklist was reviewed on 80 construction workers. They were divided into two groups of 30 and 50. The questionnaire was completed at intervals of 3-7 days in two rounds. Results The Persian version of QEC questionnaire was reported with easy terminology, wordage, and phrases. Interpreters were also unanimous about this, and the quality of translation was clearly translatable , the use of common language, conceptual equivalence, and the overall quality of translation was desirable. And the interpreter's agreement was satisfactory. In other words, the results of the formal validity check showed that all items were approved. High levels of internal consistency (α=0.74), inter-rater reliability (r=0.79-0.93) and intra-rater reliability (r=0.74-0.89) were obtained, too. Face validity had acceptable results from both workers and specialists' perspective. In addition, SEM scale for inter-rater (4.9-0.4), intra-rater (2.8-0.73) showed low random errors.  Conclusion Questionnaire was verbally verified in a way that all 16 questions were clear, simple, and understandable with acceptable reliability. Therefore, The QEC can be applied as a specific risk assessment instrument for industrial and research studies in Persian language populations.